2004
DOI: 10.1080/1028602031000119763
|View full text |Cite
|
Sign up to set email alerts
|

Bowdichine, a new diaza-adamantane alkaloid from Bowdichia virgilioides

Abstract: A novel alkaloid named bowdichine (1), only the third with a diaza-adamantane skeleton containing an unusual N-acetyl enamine moiety, and the known alkaloids acosmine (2), ormosanine (3) and podopetaline (4) have been isolated from the stem bark of Bowdichia virgilioides. The structures were elucidated on the basis of spectral data, mainly 1D and 2D NMR of the diaza-adamantane alkaloids 1 and 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 9 publications
0
11
0
2
Order By: Relevance
“…Phytochemical studies carried out on the bark and root materials have revealed the presence of tannins and lupeol (Calle et al 1983), alkaloids and terpenoids (Torrenegra et al 1985, Marinho et al 1994, volatile constituents and flavonoids (Arriaga et al 1998, Veloso et al 1999 and dihydrobenzofuran (Melo et al 2001). There were also reports of a novel alkaloid named bowdichine and two new isoflavonoids from the stem bark of this plant (Barbosa-Filho et al 2004, Juck et al 2006. To the best of our knowledge, no scientific reports on the anti-610 WANDER M. BARROS et al inflammatory or analgesic effects of this plant were so far available.…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical studies carried out on the bark and root materials have revealed the presence of tannins and lupeol (Calle et al 1983), alkaloids and terpenoids (Torrenegra et al 1985, Marinho et al 1994, volatile constituents and flavonoids (Arriaga et al 1998, Veloso et al 1999 and dihydrobenzofuran (Melo et al 2001). There were also reports of a novel alkaloid named bowdichine and two new isoflavonoids from the stem bark of this plant (Barbosa-Filho et al 2004, Juck et al 2006. To the best of our knowledge, no scientific reports on the anti-610 WANDER M. BARROS et al inflammatory or analgesic effects of this plant were so far available.…”
Section: Introductionmentioning
confidence: 99%
“…AGRA et al and podopetaline (Barbosa-Filho et al 2004). The antimicrobial property from B. virgilioides has been attributed to its essential oil of seeds (Almeida et al 2006) and leaves (J.G.R.…”
mentioning
confidence: 99%
“…Several phytochemical studies of this species disclosed the presence of alkaloids (4,(7)(8)(9), flavonoids (3,(10)(11)(12), benzofuranoids (11,13) and triterpenoids (13)(14)(15). In previous works, the essential oil from the fruits of B. virgilioides showed a high percentage of farnesol, geraniol and b-caryophyllene (16), while Arriaga et al (17) reported the presence of 4-ethyl-2-methoxyphenol (11%), 2-tridecanone (54.6%) and 2-pentadecanone (9 %) as major compounds in the oil of the roots harvested from Ceará state, Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Bowdichia vigilioides seeds are used in Brazilian folk medicine to treat rheumatism, arthritis, skin diseases, blood purification, diabetes and malaria (2)(3)(4)(5)(6). Several phytochemical studies of this species disclosed the presence of alkaloids (4,(7)(8)(9), flavonoids (3,(10)(11)(12), benzofuranoids (11,13) and triterpenoids (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%